Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 32. Beitrag. Lepidoptera: Sphingidae. - Eichler, Franz; Friese, Gerrit (Contributions to Entomology = Beiträge zur Entomologie, 1965)
This paper gives a survey of the Sphingidae of South East Europe and a list of the species at present identified in Albania. The material on Sphingidae collected by the expedition to Albania by Deutsches Entomologisches Institut and in a previous expedition by Friese contained 12 specimens and 12 observation data of 6 species. The first finding of Laothoe populi (Linne) in Albania is noted. Now a total of 15 species of Sphingidae is known from Albania.